Mapping Regional Differences of Local Pressure-Volume Curves With Electrical Impedance Tomography. Issue 4 (April 2017) - Beda, Alessandro; Carvalho, Alysson R.; Carvalho, Nadja C.; Hammermüller, Sören; Amato, Marcelo B. P.; Muders, Thomas; Gittel, Claudia; Noreikat, Katharina; Wrigge, Hermann; Reske, Andreas W.
Abstract : Objectives: Lung-protective mechanical ventilation aims to prevent alveolar collapse and overdistension, but reliable bedside methods to quantify them are lacking. We propose a quantitative descriptor of the shape of local pressure-volume curves derived from electrical impedance tomography, for computing maps that highlight the presence and location of regions of presumed tidal recruitment (i.e., elastance decrease during inflation, pressure-volume curve with upward curvature) or overdistension (i.e., elastance increase during inflation, downward curvature). Design: Secondary analysis of experimental cohort study. Setting: University research facility. Subjects: Twelve mechanically ventilated pigs. Interventions: After induction of acute respiratory distress syndrome by hydrochloric acid instillation, animals underwent a decremental positive end-expiratory pressure titration (steps of 2 cm H2 O starting from ≥ 26 cm H2 O). Measurements and Main Results: Electrical impedance tomography-derived maps were computed at each positive end-expiratory pressure-titration step, and whole-lung CT taken every second steps. Airway flow and pressure were recorded to compute driving pressure and elastance. Significant correlations between electrical impedance tomography-derived maps and positive end-expiratory pressure indicate that, expectedly, tidal recruitment increases in dependent regions with decreasing positive end-expiratory pressure ( p < 0.001) and suggest that overdistension increases both at high and low positive end-expiratory pressures in nondependent regions ( p < 0.027), supporting the idea of two different scenarios of overdistension occurrence. Significant correlations with CT measurements were observed: electrical impedance tomography-derived tidal recruitment with poorly aerated regions ( r = 0.43; p < 0.001); electrical impedance tomography-derived overdistension with nonaerated regions at lower positive end-expiratory pressures and with hyperaerated regions at higher positive end-expiratory pressures ( r ≥ 0.72; p < 0.003). Even for positive end-expiratory pressure levels minimizing global elastance and driving pressure, electrical impedance tomography-derived maps showed nonnegligible regions of presumed overdistension and tidal recruitment. Conclusions: Electrical impedance tomography-derived maps of pressure-volume curve shapes allow to detect regions in which elastance changes during inflation. This could promote individualized mechanical ventilation by minimizing the probability of local tidal recruitment and/or overdistension. Electrical impedance tomography-derived maps might become clinically feasible and relevant, being simpler than currently available alternative approaches. Abstract : Supplemental Digital Content is available in the text.